In-kind transfers as insurance - Lucie Gadenne; Samuel Norris; Monica Singhal; Sandip Sukhtankar (Institute for Fiscal Studies (IFS), 2022)
In-kind transfers can provide insurance benefits when prices of consumption goods vary, as is common in developing countries. We develop a model demonstrating that in-kind transfers are welfare improving to beneficiaries relative to cash if the covariance between the marginal utility of income and price is positive. Using calorie shortfalls as a marginal utility proxy, we find that in-kind transfers are preferred for low-income Indian households. Expansions in India's flagship in-kind food transfer program not only increase caloric intake but also reduce caloric sensitivity to prices. Our results contribute to ongoing debates about the optimal form of social protection programs.
Keywords: H42; H53; I38; O12; Q18; 330; in-kind transfers; cash transfers; price risk; Public Distribution System; India